Climate projections over the Antarctic Peninsula region to the end of the 21st century. Part ІІ: wet/dry indices - Chyhareva, A.; Krakovska, S.; Pishniak, D. (Український антарктичний журнал, 2019)
Objective of the study is an assessment of possible climate change in the region of the Antarctic Peninsula from 1986 until the end of the 21st century projected by the RCMs’ ensemble. During the last decades Antarctica has undergone predominantly warming, with the highest rate of surface air temperature increase found over the Antarctic Peninsula, where the Ukrainian Antarctic Akademik Vernadsky station is located. There is a unique ecosystem in the region which is vulnerable and under the growing impact of a changing weather regime due to rapid climate changes with consequent changes in sea ice, land distribution under snow/ice, etc. Thus, an important task for the region is an estimation of climate change trends and definition of possible subregionalization. Мета дослідження — оцінка можливої зміни клімату в регіоні Антарктичного півострова до кінця 21 століття за проекціями ансамблю регіональних кліматичних моделей (РКМ). Впродовж останніх десятиліть на переважаючій території Антарктиди спостерігається потепління, воно найінтенсивніше для Антарктичного півострова, де знаходиться Українська антарктична станція «Академік Вернадський». У регіоні існує унікальна екосистема, яка є вразливою до зміни погодного режиму, що відбувається під впливом швидких змін клімату та їхніх наслідків, зокрема, зміни розподілу морського льоду та суші вкритої снігом / льодом тощо. Отже, для регіону важливим завданням є оцінка проекцій зміни клімату з визначенням окремих районів з подібними тенденціями.